x-(2x+3)=1-3x

Simple and best practice solution for x-(2x+3)=1-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(2x+3)=1-3x equation:


Simplifying
x + -1(2x + 3) = 1 + -3x

Reorder the terms:
x + -1(3 + 2x) = 1 + -3x
x + (3 * -1 + 2x * -1) = 1 + -3x
x + (-3 + -2x) = 1 + -3x

Reorder the terms:
-3 + x + -2x = 1 + -3x

Combine like terms: x + -2x = -1x
-3 + -1x = 1 + -3x

Solving
-3 + -1x = 1 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-3 + -1x + 3x = 1 + -3x + 3x

Combine like terms: -1x + 3x = 2x
-3 + 2x = 1 + -3x + 3x

Combine like terms: -3x + 3x = 0
-3 + 2x = 1 + 0
-3 + 2x = 1

Add '3' to each side of the equation.
-3 + 3 + 2x = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 1 + 3
2x = 1 + 3

Combine like terms: 1 + 3 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 4+4v=-12 | | z^2+y^2+x^2=8x | | -4w+2(w-3)=6 | | (x+15)+110=180 | | 5b+11=56-46 | | 8X-15X-30X-51X=53X+172 | | -7W-4w-1-9w= | | -11=-7v+4(v+4) | | -1(18z-11)=15 | | 8(w-4)=-9w-49 | | 176=-16t^2+114t+6 | | 400x+.04=250x+.18 | | x+23+105=180 | | S/=p | | -2x+(5x-1)=x-1 | | 3x^2+10-144=0 | | -4(3n-1)=20 | | n/8-3=-9 | | t+9T+T+T= | | 20=4-(y+7) | | 3x^2+67x-146=0 | | 6-10c-1=4-4c | | -12=4u+4 | | 2(v+1)=3v+23 | | 3(x+5)+6=-6 | | 1/3x^2-10x | | -2a+7=-23 | | 3(y+4)-2y=2(y+1) | | (2x+4)9=(3x-30)9 | | 2(v+1)=3u+23 | | x=3x+6x-9 | | x^3-6x^2-20x+120=0 |

Equations solver categories